Espiritualidade eco-relacional no contexto da formação docente: experiências pedagógicas dialógicas em escolas de ensino médio em tempo integral do Ceará - Mesquita, José Rinardo Alves (2021)
This thesis presents an action – intervention in the continuous formation process of teachers from two full-time schools of Ceara state education network located in Itapipoca city. Although, teacher training practices in state public schools bring some concerns with the socio-emotional aspects, they are still based on cognitives aspects, restricting teacher training and performance to technical, bureaucratic and conceptual dimensions. Therefore, the perspectives of this study are situated in the systematization of an experimental process experienced in permanent practices of teachers training that occur within the school space having as guiding axis Dialogic Pedagogical Experiences that put in evidence the dimension of spirituality in an Eco-relational perspective – ERP. Thus, our main goal was to understand the implications of Dialogic Pedagogical Experiences in Eco-relational spirituality within teachers training process starting from perspectives of teachers. The main theoretical dimensions that supported our study were: the dialogic education from Paulo Freire, the eco-relational perspective – ERP from João Figueiredo, the ongoing relacional formation from Eleni Henrique, ecological, relational and naturalized spirituality from Leonardo Boff and Robert Solomon, and the concepts of experiences were brought up by Larossa, Josso, Dewey, Macedo and Benjamin. The weaving of the chosen methodological path was anchored in the engaged research proposed by Figueiredo who strives for the collective construction of training processes, dialogicity, loving- kindness, multiple languages, contextualization and an integrated view of relationships. The research took place through eco-relational experiential meetings on these two schools during 2019 and early 2020 with 30 (thirty) teachers from different fields of knowledge, and as a data collection procedure: speech transcription through dialogical circles, photographic records, speech recordings during the process, analysis of the participant researcher's logbook. From this experiential-theoretical-methodological construct on, we were able to support possible paths to think about a multidimentional, emancipatory, relational, lovingly political, with primacy the dimension of an eco-relational spirituality.